Generating 3 Dimensional Pavilions Described in Mayamatam; a Traditional Indian Architecture Treatise. (March 2013) - Garg, Yogesh K.; Das, Vinay M.
The traditional or classical architecture of India is an interesting subject for exploration from different perspectives. Taking pavilions described in Mayamatam as a representative of the traditional or classical architecture of India and analyzing them from the viewpoint of pattern recognition and mathematics encouraging results are obtained. A pattern is seen in the development of the design of pavilions and has been coded alpha-numerically. Based on the system of development and employing computer applications software is created to design pavilions, which follow the principles of traditional architecture. This software has multiple benefits. It can be used as a teaching aid for the subject 'history of Indian Architecture'. For architectural conservationists and heritage enthusiasts it offers itself as a tool to help in visualization and digital reconstruction. For architects it can be a means for making structures of recent times, which have the essence of traditional architecture. The aim of this paper is to highlight the methodology for preparing this software and demonstrating its output.